أثرالثقافة الحضرية على الأسرة في المدينة الأسرة السوفية أنموذجا - هادفي تاج الدين; بن عيسى رابح (University of Eloued جامعة الوادي, 2024)
تهدف هذه الدراسة لمحاولة التعرف على أثر الثقافة الحضرية للأسرة السوفية في الأحياء السكنية الجديدة مبرزين في ذلك أهم التغيرات والتحولات التي طرأت عليها من حيث أشكالها ووظائفها ونمط علاقاتها الاجتماعية, وما انعكس عنها من أثار ومظاهر ثقافية جديدة من جراء أسلوب الحضرية على بنيتها الداخلية, وقد بينت هذه الدراسة أن للثقافة الحضرية دورا مهما في تغير الأسرة السوفية بالأحياء السكنية الجديدة, حيث تغيرت من أسرة ممتدة إلى أسرة نووية, نقص السلطة الأبوية, وخروج المرأة للعمل, تقسيم الأدوار على مستوى أفراد الأسرة, أما على مستوى العلاقات الاجتماعية فقد تميزت بالسطحية والمصلحة الخاصة بين الأفراد . Abstract: This study aims to try to identify the impact of the urban culture of the Sofiet family on the new residential neighborhoods, highlighting the most important changes and transformations that occurred in it in terms of its forms, functions, and the pattern of its social relations, and the new cultural effects and manifestations reflected in it as a result of the urban style on its internal structure. This study shows that urban culture has an important role in the change of the Sofiet family in the new residential neighborhoods, as it changed from an extended family to a nuclear family, lack of paternal authority, and women going out to work, division of roles at the level of family members, but at the level of social relations it was characterized by superficiality and special interest between individuals
Keywords: تحضر; حضرية; ثقافة حضرية; أسرة; مدينة; urbanization; urban area; urban culture; family; city